EMPIRICAL ANALYSIS OF DEPOSIT MONEY BANKS CUSTOMERS’ SOPHISTICATION IN YOLA, ADAMAWA STATE, NIGERIA. - Bashir Ahmad Daneji; Ahmad Aminu Hamidu; Adamu Magaji Abubakar; Mahmoud Ahmad Mahmoud (Universitas Kuningan, 2020)
Purpose – the purpose of this paper to investigate customer sophistication of deposit money banks in Yola, Adamawa state, Nigeria.Design/methodology/approach – this study adopts the quantitative survey method with a sample of 375 deposit money banks customers from Yola metropolis using purposive sampling technique. Similarly, PLS-SEM approach was used in data analysis to confirm validity of the model and subsequently analyze the structural model for obtaining the path analysis.Findings – Relationship between search orientation, and market experience are approximately equal in terms of positive strength, while innovativeness of customers emerged as the least in terms of strength in positive relationship. Customers are therefore less innovative when it comes to general knowledge and experience in evaluating the prospects of different options. Brand value orientation is also a strong determinant of customer sophistication because respondents are more attached to brands they are more familiar with than taking brand of services that are new and becoming more risk averse. Customer sophistication in general to the respondents indicates moderate satisfaction with services and low self-image and esteem.Practical implications – customers are less sophisticated because they lack innovativeness and stick to brand value orientation, they don’t realize full satisfaction, self-image and attainment of self-esteem as an experienced customer. Therefore, deposit money banks need to consider the findings of this study to improve customer sophistication.Originality/value – this study is the first of its kind in the contest of the study.